Research on Grinding Parameters of Parts with Same Clamping Mode and Different Sizes - Zhang, Hua; Chen, Hua; Hu, Lai (Manufacturing Technology Journal, 2022)
Aiming to study the influence of ultra-precision grinding parameters on the accuracy between the same clamping method and different workpiece sizes. This paper mainly analyzes the difference between the measurement precision of different parts by the same measurement method and the measurement precision of the same parts by different measurement methods. Therefore, the influence of grinding parameters on grinding precision is reflected. For the same part, it is concluded that the coaxiality error coincidence degree at end A and end B reaches 90.32% and 95.27%, respectively by using precision three-coordinate measuring instrument and Mahr roundness instrument. The coincidence degree of end A and end B verticality error reached 97.54% and 91.08%, respectively. For parts with different sizes, the Mahr roundness meter is used for measurement. The analysis shows that the coaxiality coincidence at end A and end B is the highest, reaching 98.36% and 92%, respectively. And from the analysis, the errors are mainly reflected in the factors such as jig and fixture and grinding process.
Keywords: Ultra-precision/ultra-high speed grinding; Grinding parameters; Optimization; Precision error